تقييم مستوى الفهم الشفهي لأطفال عرض داون (دراسة مقارنة بين الأطفال المدمجين بالأقسام الخاصة والأطفال غير المدمجين بالمراكز النفسية البيداغوجية - مريم لعرابي; شيماء قرادي; بن يطو جلول (My University, 2023)
The current study dealt with the issue of assessing the level of oral comprehension in children with Down syndrome a comparative study of merged children in primary and non-integrated schools located in the psychological and pedagogical centers in the city of Laghouat. :The hypotheses of the study were as follows General hypothesis: there are statistically significant differences of oral comprehension among children between with Down syndrome in psychological pedagogical centers and their peers who are integrated into the special sections of primary schools. Partial hypotheses: There are statistically significant differences in degrees of comprehension between the study sample is attributed to the gender variable Oral There are statistically significant differences in the oral comprehension scores of the study sample due to a variable. And we followed Descriptive method to suit the subject of the study And we used as a study tool the man's drawing test To determine the mental age of the study sample and test khomssi ELO To assess oral language adapted to the Algerian environment from Ada Dalila The understanding item was selected on a sample of 40 male and female children Our findings were based on the hypotheses that we set out from It turned out that there were no differences between the results of the study sample. Key words: Oral comprehension / Down’s syndrome / school integration / Oral language test ( Elo)